2022
DOI: 10.1038/s41598-022-07309-x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-in-Thousands by sequencing panel development and application for high-resolution monitoring of introgressive hybridization within sockeye salmon

Abstract: Stocking programs have been widely implemented to re-establish extirpated fish species to their historical ranges; when employed in species with complex life histories, such management activities should include careful consideration of resulting hybridization dynamics with resident stocks and corresponding outcomes on recovery initiatives. Genetic monitoring can be instrumental for quantifying the extent of introgression over time, however conventional markers typically have limited power for the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 58 publications
(79 reference statements)
1
8
0
Order By: Relevance
“…We designed our SNP selection and validation workflow to construct a GT‐seq panel for effectively identifying and sexing individuals, as well as estimating pairwise kinship up to third‐order relationships. Other recent applications of multi‐scaled GT‐seq panels include identifying individuals and reconstructing population structure in polar bears (Hayward et al, 2022 ) and rattlesnakes (Schmidt, Govindarajulu, et al, 2020 ), and identifying life history forms, assigning stock, and reconstructing population history in kokanee salmon (Chang et al, 2022 ; Setzke et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We designed our SNP selection and validation workflow to construct a GT‐seq panel for effectively identifying and sexing individuals, as well as estimating pairwise kinship up to third‐order relationships. Other recent applications of multi‐scaled GT‐seq panels include identifying individuals and reconstructing population structure in polar bears (Hayward et al, 2022 ) and rattlesnakes (Schmidt, Govindarajulu, et al, 2020 ), and identifying life history forms, assigning stock, and reconstructing population history in kokanee salmon (Chang et al, 2022 ; Setzke et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping‐in‐Thousands by sequencing (GT‐seq; Campbell et al, 2015 ) is a MTAS approach currently available that has seen widespread utility across studies in ecology, evolution, and conservation (Chang et al, 2021 , 2022 ; Hayward et al, 2022 ; Jo et al, 2021 ; Natesh et al, 2019 ; Schmidt et al, 2020 ; Setzke et al, 2021 ; Sjodin et al, 2020 ). Here, we employed a scalable workflow to develop a GT‐seq panel for invasive Sitka black‐tailed deer in Gwaii Haanas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome‐wide studies based on reduced‐representation approaches have identified a handful of single nucleotide polymorphisms (SNPs) exhibiting putative signatures of divergent selection among O. nerka migratory and reproductive ecotypes (Christensen et al, 2020; Larson et al, 2017; Lemay & Russello, 2015; Nichols et al, 2016; Veale & Russello, 2017a), with perhaps the most notable being an SNP in LRRC9 on LG12 showing a strong association with stream/river‐spawning and shore/beach‐spawning in both sockeye and kokanee (Veale & Russello, 2017b). These previous studies, however, were limited to the analysis of sequence variation and by their sparse coverage of the genome, constraining their ability to more fully characterize the genomic basis and architecture of these life history traits, including SVs that could maintain reproductive and migratory life history differentiation among ecotypes in the presence of gene flow (Chang et al, 2022; Elliott et al, 2020; Veale & Russello, 2016, 2017a). In fact, testing the role of SVs in life history variation in sockeye/kokanee is particularly timely as evidence for an important contribution of SVs in maintaining ecotypic differentiation in salmonids varies by species: for example, while a well‐characterized double‐inversion is associated with sex‐specific migratory tendency in rainbow trout ( Oncorhynchus mykiss ; Pearse et al, 2019), a block of highly differentiated SNPs spanning ~140 kb and controlling migratory timing in Chinook salmon ( Oncorhynchus tshawytscha ) does not appear to be maintained by an inversion or other SVs (Thompson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we analysed sequence and structural variation from short‐ and long‐read whole genome resequencing data to investigate the genomic basis and architecture of reproductive and migratory behaviour, focusing on a system where sockeye and kokanee populations share recent common ancestry (Beacham & Withler, 2017; Taylor et al, 1996; Veale & Russello, 2017a) and where stream‐spawning and shore‐spawning kokanee co‐occur (Okanagan Lake/River, British Columbia, Canada). Given the complexity of the traits under divergent selection and evidence of gene flow among O. nerka ecotypes (Chang et al, 2022; Elliott et al, 2020; Veale & Russello, 2016), we hypothesized the following: (i) the genetic basis of ecotypic differentiation involves many genes of different functions; (ii) the underlying genetic architecture is polygenic, with numerous, tightly linked variants (SNPs and/or SVs); and (iii) large SVs maintain clusters of differentiated loci associated with migratory and reproductive behaviour.…”
Section: Introductionmentioning
confidence: 99%